2022
DOI: 10.1093/ntr/ntac135
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Covid-19 Pandemic on Smoking Among Vulnerable Populations

Abstract: Aim While accumulating evidence suggests that people modified their smoking during the ongoing COVID-19 pandemic, it remains unclear whether those most at risk for tobacco-related health disparities did so. The current study examined changes in smoking among several vulnerable smoker populations during the COVID-19 pandemic. Methods A web-based survey was distributed in 2020 to 709 adults with socioeconomic disadvantage, affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Some studies showed that more smokers increased the use of tobacco products ( 8 , 9 ), while some showed more decrease in use ( 10 , 11 ). While most social distancing measures decreased the use of tobacco products, unemployment and anxiety may increase the use of tobacco products ( 12 , 13 ). Masking is an impact factor that might cause the reduction of smoking or quitting ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed that more smokers increased the use of tobacco products ( 8 , 9 ), while some showed more decrease in use ( 10 , 11 ). While most social distancing measures decreased the use of tobacco products, unemployment and anxiety may increase the use of tobacco products ( 12 , 13 ). Masking is an impact factor that might cause the reduction of smoking or quitting ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, participants faced some psychological issues following the outbreak of the pandemic. It was reported that higher levels of anxiety among patients may lead to increased tobacco consumption [38]. In another study, 18.5% of smokers reported lower cigarette consumption and 13.8% reported higher cigarette consumption following the pandemic [20].…”
Section: Discussionmentioning
confidence: 93%
“…For example, a Californian study confirmed higher use of cigarettes during lockdown, which was explained by increased stress, changes in workplace, and increased opportunities for smoking or vaping (Gonzalez, Epperson, Halpern-Felsher, Halliday, & Song, 2021). Supportively, another US study noted an increase in smoking during the COVID-19 pandemic at the sample of adults from vulnerable populations, indicating unemployment and anxiety as factors which could contribute to greater risk of tobacco use (Wiley et al, 2023). Finally, a very comprehensive UK study discussed increased smoking as a coping mechanism to deal with anxiety, boredom, stress, and anger during the COVID-19 lockdown (Grogan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%